IMPROVING THE COMPETENCE OF TEACHERS IN PREPARING LEARNING IMPLEMENTATION PLAN BASED ON CHARACTER REINFORCEMENT THROUGH THE USE OF MEDIA IN SDN LONTAR II SURABAYA - Romlah Romlah (LPPM STAI Muhammadiyah Probolinggo, 2020)
This research is a school action research that will be conducted in 2 (two) cycles. There are 4 stages in each cycle; 1) action planning, 2) action implementation, 3) observation and inter-presentation of action, followed by analysis and evaluation, and 4) reflection. The subjects in this study were ten homeroom teachers and two training teachers at SDN Lontar II Surabaya. A supervision with teaching demonstration techniques was conducted in an effort to improve the ability of homeroom teachers in implementing learning activities by using the CD player and the flash animation media at SDN Lontar II Surabaya. It can be seen from the level of teacher's ability in cycle I and cycle II within each aspect respectively. In Aspect 1, the value is increased from 63% in cycle I to 73.7% in using LCD Projector as learning media. In Aspect 2, the ability of teachers to plan learning activities increased from 58.7% in the first cycle to 71.5% in cycle II. In Aspect 3, teacher's ability in creating class activities during the lesson increased from 61.8% to 76.3% in cycle II. The applied clinical discipline is able to overcome their difficulties and constraints in planning the learning process because of its collegial nature. There is no effective pressing instruction other than a conducive discussion or interaction.